Genetic Variability and Character Association in Acacia catechu Willd - Gera, Mohit; Gera, Neelu (Indian Forester, 2006)
Twenty genotypes of Acacia catechu Willd. scattered over Jammu region in their natural range were studied for the pattern of genetic variation. Higher values of genotypic varianceand genotypic coefficient of variation as compared to environmental variance and environmental coefficient of variation in germination and growth characters, indicating that they are under genetic control. The heritability and expected genetic gain were also observed to be high for these characters, except germination per cent. The correlations between germination per cent, seedling height, collar diameter and biomass at phenotypic level were positive and significant. The families F4, F5, F12, F13, F14 and F15 exhibited good performance and are recommended for further genetic improvement program in this species. The positive relationship between dbh of the CPT and the important parameters of the progeny, i.e, seed weight, germination per cent and seedling height can be utilized for meeting the interim seed requirement of the species as the seed collected from the trees with higher dbh is expectedto perform better at nursery stage